Identification of a complete dibenzothiophene biodesulfurization operon and its regulator by functional metagenomics. (21st October 2019) - Martín‐Cabello, Guadalupe; Terrón‐González, Laura; Ferrer, Manuel; Santero, Eduardo
Summary: Functional screening for aromatic ring oxygenases of an oil contaminated soil metagenome identified 25 different clones bearing monooxygenases coding genes. One fosmid bore an operon containing four tightly linked genes coding for a complete dibenzothiophene biodesulfurization pathway, which included the predicted monooxygenases DszC and DszA, the desulfinase DszB, and an FMN‐oxidoreductase designated DszE. The dszEABC operon provided Escherichia coli with the ability to use dibenzothiophene as the only sulfur source. Transcription of the operon is driven from a σ N ‐dependent promoter and regulated by an activator that was designated dszR . DszR has been purified and characterized in vitro and shown to be a constitutively active σ N ‐dependent activator of the group IV, which binds to two contiguous sequences located upstream of the promoter. The dsz promoter and dszE and dszR genes have apparently been recruited from an aliphatic sulfonate biodegradation pathway. If transcribed from a heterologous upstream promoter, the σ N ‐dependent promoter region functions as an 'insulator' that prevents translation of dszE, by binding with its ribosome binding site. Translational coupling, in turn, prevents translation of the downstream dszABC genes. The silencer combined with translational coupling thus represents an effective way of preventing expression of operons when spuriously transcribed from upstream promoters.